Development Of Caulis Extract (Tinospora Crispa (L.) Hook. F. & Thomson As Plasmodium In Preparations Tablets - Patimah Patimah; Junie Suriawati; Siti Rahayu Rahmawati (Politeknik Kesehatan Kemenkes Jakarta II, 2018)
Brotowali (Tinospora crispa (L.) Hook. f. Thomson is a wild plant & in the Woods, fields or planted page near the fence, and the usual planted as medicinal plants. The entire plant (roots, stems, and leaves) has a bitter taste that can be used as a traditional medicine as Plasmodium. This research aims to make the tablet dosage of Caulis extract with gelatin Binder and polivenilpirolidon materials that meet the requirements of the physical quality of a tablet that is acceptable. Prior to the manufacture of tablets do extract raw materials testing which includes the determination of the levels of ash, determination of microbial impurities, testing the determination of aflatoxin levels of impurities, the determination of the levels of pesticide residues, the determination of the level of heavy metal impurities. Caulis extract tablet manufacture is made with two formula with each different binding materials, namely formula I used gelatin formula II 5% and 5% use polivinilpirolidon. The methods used in the manufacture of Caulis extract tablets using a wet granulation method. Granul tested his physical properties obtained covering moist, flow properties, compressibility granule. Tablets obtained physical quality test performed which include uniformity of weight, hardness, size uniformity, compressibility, and the crushed tablets. The data obtained were analyzed statistically using SPSS 15.0 for windows program namely testing T-Test with a 5% confidence. The results showed that the two formula tablets with the uniformity of weight, hardness, size uniformity, compressibility, and the time crushed tablet that meets the requirements of the physical quality of a good tablet. The conclusions of this research are extracted Caulis tablet can be created that meets the requirements of physical quality test tablet.